Respuesta :

Answer:

The answer to your question is   3x - y = 3P - Q  

Step-by-step explanation:

Process

1.- Get the points from the graph of the original line

A (0, 5)

B (-3, 6)

2.- Find the slope of the original line

[tex]m = \frac{y2 - y1}{x2 - x1}[/tex]

Substitution

[tex]m = \frac{6 - 5}{-3 - 0} = \frac{-1}{3}[/tex]

3.- Find the slope of the new line

As the lines are perpendicular the new slope will be

      m = 3

4.- Find the equation of the new line

Point (P, Q)

Equation            y - y1 = m(x - x1)

Substitution

                          y - Q = 3(x - P)

Simplify

                          y - Q = 3x - 3P

Result

                          3x - y = 3P - Q